2011
DOI: 10.1111/j.1439-0531.2011.01812.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress Preconditioning of Boar Spermatozoa: A New Approach to Enhance Semen Quality*

Abstract: Contents Semen preparation and cryopreservation require finely adjusted procedures. Gametes are sensitive to environmental stresses, so in vitro procedures aim to minimize the inevitable harmful conditions. Applying stress to precondition cells has only been investigated recently. Studies demonstrated that by utilizing a well defined and properly applied hydrostatic pressure (HP) stress treatment to spermatozoa before in vitro storage, cryopreservation or insemination, cell survival and fertility improved comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Nevertheless, in literature, there are other reports describing cryotolerance improvement of boar and bull spermatozoa following hydrostatic pressure challenge [42,45,46].…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, in literature, there are other reports describing cryotolerance improvement of boar and bull spermatozoa following hydrostatic pressure challenge [42,45,46].…”
Section: Discussionmentioning
confidence: 95%
“…ROS Mitochondrial uncoupling separates oxidative phosphorylation from adenosine triphosphate 35 (ATP) synthase with energy dissipated as heat, and incomplete or mild mitochondrial uncoupling 36 has been shown to reduce oxidative damage [9]. For example, uncoupling induced by the 37 chemical protonophore 2,4-dinitrophenol (DNP) has been shown to be beneficial for in vitro 38 culture of porcine and bovine embryos [31; 45], and for sperm cryopreservation in rhesus 39 macaques [14] and yellow catfish [19]. Physiological uncoupling is mediated by protein 40 complexes embedded in the mitochondrial inner membrane, most notably the uncoupling 41 proteins (UCPs) [3; 42].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…A study involving 7 hybrid boars has shown that stressing semen with hydrostatic pressure compared to conventional processing resulted in higher progressive motility [103]. In a second part of the latter study, each ejaculate of 14 hybrid boars was split in two and either treated by hydrostatic pressure or processed normally.…”
Section: Managing the Ejaculate: Factors During Semen Handlingmentioning
confidence: 99%